Insights in Anaphylaxis and Clonal Mast Cell Disorders - González-de-Olano, David; Álvarez-Twose, Iván (Frontiers in Immunology, 2017)
The prevalence of anaphylaxis among patients with clonal mast cell disorders (MCD) is clearly higher regarding general population. Due to a lower frequency of symptoms outside of acute episodes, clonal MCD in the absence of skin lesions might sometimes be difficult to identify which may lead to underdiagnosis, and anaphylaxis is commonly the presenting symptom in these patients. Although the release of mast cell (MC) mediators upon MC activation might present with a wide variety of symptoms, particular clinical features typically characterize MC-mediator release episodes in patients with clonal MCD without skin involvement. Final diagnosis requires a bone marrow study and it is recommended that this should be done in reference centres. In this article, we address the main triggers for anaphylaxis, risk factors, clinical presentation, diagnosis and management of patients with mast cell activation syndromes, with special emphasis on clonal MCAS (systemic mastocytosis and mono(clonal) mast cell activations syndromes).